Microbial and phytochemical approaches to mosquito control: A review focusing on Lysinibacillus sphaericus and Sphagneticola trilobata: Modern Bio-Science to Combat Vector Borne Disease - Rani, NA; Robin, TB; Hossain, FMA; Hasanuzzaman, M; Zinnah, KMA (Journal of the Sylhet Agricultural University, 2025)
Mosquito-borne diseases such as malaria, dengue, Zika virus, chikungunya, and yellow fever continue to pose significant threat for global public health. Traditional chemical pesticides, is somewhat effective to control mosquito populations, but has severe environmental concerns, such as damaging ecology, harmful for beneficial non-target animals, and an alarming increase in insecticide-resistant mosquito strains. Our review sheds light on microbiological and phytochemical approaches to mosquito control as effective and environmentally sustainable option. Lysinibacillus sphaericus. A gram-positive soil bacterium has great effectiveness as a biocontrol candidate because it generates specific larvicidal toxins such as the binary toxin complex (BinA and BinB) and mosquitocidal toxins (Mtx). These poisons selectively target mosquito larvae midgut cells and have no major impact on non-target species, making L. sphaericus a vital part in integrated vector management schemes. Phytochemical approaches disrupt crucial mosquito life cycle pathways using plant-derived bioactive chemicals. Sphagneticola trilobata, a widely distributed tropical plant, has demonstrated substantial potential in mosquito control as it contains a great range of bioactive compounds, including flavonoids, terpenoids, saponins, and phenolic acids. These substances have larvicidal, insecticidal, and repellant activities through an involvement with mosquito digestion, hormonal balance, and neural pathways. S. trilobata extracts are also a sustainable, biodegradable, and environmentally friendly alternative to synthetic insecticides. This analysis highlights L. sphaericus and S. trilobata's promise as eco-friendly and effective solutions to the expanding mosquito control difficulties by investigating their mechanisms of action, practical uses, and environmental advantages. J. Sylhet Agril. Univ. 11(2): 19-28, 2024